Long Memory and Disaggregated Energy Consumption: Evidence from Fossils, Coal and Electricity Retail in the U.S. - Apergis, Nicholas; Tsoumas, Chris (Elsevier, 2012)
In this paper, the long memory properties of disaggregated fossils, coal and electricity retail consumption in the U.S. over the 1989–2009 period are examined. The presence of long memory is related to autocorrelation persistence of each series. Our results show that there is heterogeneity in the order of integration between these types of energy consumption and for the different sectors employed, which is affected by the inclusion of a break event. The order of integration was generally higher for the case of a break in the intercept than in the slope, with the latter being more plausible for all series.